عقد التأمين البحري في ضوء التزامات المؤمن والمؤمن له دراسة مقارنة - Resen Abdulsahib , Dr. Kadhim (Basra studies journal, 2026)
The Marine insurance contract, like any other contract, is based on reciprocal obligations between its parties—the insurer and the insured—and is grounded in the principle of consent and the modern rules of attribution, which constitute the legal basis for such contracts. The relationship between insurance companies and the other party (the insured, who may be a natural or legal person) is evident in cases such as shipping companies, which may own the vessel or the cargo transported on board. The insurer is obligated to compensate for losses that may occur to the insured property, provided that the insured has fulfilled their financial obligations under the contract. These obligations include the payment of marine insurance premiums as specified in the contract, as well as the obligation not to combine compensation from the insurer with any damages obtained through claims against third parties. The non-financial obligations include the disclosure of material facts related to potential risks affecting the insured property, enabling the insurer to properly assess the risks involved. This is referred to as the duty of disclosure and risk prevention. The compensatory nature of the marine insurance contract ensures that the insured is restored to the financial position they held prior to entering into the contract.